Development and implementation of participant safety plans for international research with stigmatised populations. Issue 8 (August 2018) - Sugarman, Jeremy; Barnes, Mark; Rose, Scott; Dumchev, Kostyantyn; Sarasvita, Riza; Viet, Ha Tran; Zeziulin, Oleksandr; Susami, Hepa; Go, Vivian; Hoffman, Irving; Miller, William C
Summary: People who inject drugs with high-risk sharing practices have high rates of HIV transmission and face barriers to HIV care. Interventions to overcome these barriers are needed; however, stigmatisation of drug use and HIV infection leads to safety concerns during the planning and conduct of research on such interventions. In preparing to address concerns about safety and wellbeing of participants in an international research study, HIV Prevention Trials Network 074, we developed participant safety plans (PSPs) at each site to supplement local research ethics committee oversight, community engagement, and usual clinical trial procedures. The PSPs were informed by systematic local legal and policy assessments, and interviews with key stakeholders. After PSP refinement and implementation, we assessed social impacts at each study visit to ensure continued safety. Throughout the study, five participants reported a negative social impact, with three resulting from study participation. Future research with stigmatised populations should consider using and assessing this approach to enhance safety and welfare.